ASSESSMENT OF POTENTIAL USE OF Vateria copallifera AS A FLOUR; NUTRITIONAL AND FUNCTIONAL PROPERTIES - Mihiranie, M.K.S; Jayasinghe, J.M.J.K; Wanasundara, J.P.D; Jayasinghe, C.V.L. (1st International Conference on Agriculture, Food Security & Safety, 2019)
Vateria copallifera (Sin; Hal) seeds are recognized as a healthy food source in Sri Lanka. Hal seeds have been used in the traditional food preparations as fresh scraped particles and flour made from dried hal seeds are utilized by none of the Sri Lankan people. It is worthwhile to assess the nutritional and functional properties of Hal flour to use as a potential healthy flour source for commercial food applications. Therefore, the objective of this study was to evaluate the nutritional and functional properties of Vateria copallifera flour. The nutritional properties; moisture, carbohydrate, fat, crude fiber, protein, total sugar, total starch, amylose and amylopectin content were assessed. The functional properties of flours, swelling capacity (SC), water holding capacity (WHC), oil holding capacity (OHC), emulsion activity, emulsion stability, foaming capacity, foaming stability, gelatinization temperature, least gelatinization concentration and bulk density were analyzed. Hal flour contained 8.42±4.11% moisture content, 5.21±0.003% fat content, 4.025±1.64% protein content, 1.82±0.22% mineral content, 45.67% total carbohydrate content and 3.34±0.05% crude fiber content. In addition, Vateria copallifera flour consists of 0.413±28.20% total starch content, 0.003±0.78% amylose content and 0.41% of amylopectin content. Besides that, Hal seed flour presented higher WHC (111.75±2.93%), OHC (99.68±5.92%) and SC (45.96±7.06%) which are important on food processing. Flour made from hal seeds has important nutritional and functional characteristics and therefore it can be used as a healthy flour source in the food processing and value addition.
Keywords: Vateria copallifera, flour, nutritional characteristics, functional properties